Intratympanic dexamethasone injection for sudden sensorineural hearing loss in pregnancy - Lyu, Yan-Lu (World J Clin Cases, 2020)
BACKGROUND: As sudden sensorineural hearing loss (SSNHL) rarely occurs in pregnant women, there is a lack of knowledge and relevant research on its management. AIM: To investigate the effect of intratympanic dexamethasone injection in the treatment of pregnant patients with SSNHL. METHODS: A retrospective chart review was made for the period between June 2017 and August 2019 at our Department of Otorhinolaryngology-Head and Neck Surgery. Pregnant women who met the criteria for SSNHL were included and grouped based on the therapeutic modalities. The treatment group received intratympanic dexamethasone (2.5 mg) q.o.d. for a total of four times, while the control group received no medication other than bed rest and medical observations. All the patients were under close care of obstetricians. Pure-tone audiograms were performed before and after treatment. RESULTS: Eleven patients who met the inclusion criteria were assigned to the treatment group (n = 7) and the control group (n = 4). The mean age of patients was 31.2 ± 3.8 years; the right ear was affected in seven (63.64%) cases. Two patients (18.2%) suffered from vertigo, 10 (90.9%) suffered from tinnitus and 6 (54.5%) suffered from aural fullness. The time from onset to clinic visit was relatively short, with a mean time of 1.3 ± 0.9 d. All the women were within the second or third trimester; the average gestation period was 26.0 ± 6.2 wk. The pure-tone averages at onset between the two groups were similar. After one wk of therapy, the treatment group had a curative rate of 57.1% and a significantly better hearing threshold and greater improvement compared to the control group (all P < 0.05). Some patients experienced transient discomfort from intratympanic injections that disappeared after getting rest, while none had permanent complications. All patients delivered healthy full-term neonates with an average Apgar score of 9.7 ± 0.5. CONCLUSION: Intratympanic dexamethasone injections can be used as a first-line therapy in pregnant women with SSNHL.